The PHAR-QA Project: Competency Framework for Pharmacy Practice—First Steps, the Results of the European Network Delphi Round 1 - Atkinson, Jeffrey (Pharmacy (Basel), 2015)
PHAR-QA, funded by the European Commission, is producing a framework of competences for pharmacy practice. The framework is in line with the EU directive on sectoral professions and takes into account the diversity of the pharmacy profession and the on-going changes in healthcare systems (with an increasingly important role for pharmacists), and in the pharmaceutical industry. PHAR-QA is asking academia, students and practicing pharmacists to rank competences required for practice. The results show that competences in the areas of “drug interactions”, “need for drug treatment” and “provision of information and service” were ranked highest whereas those in the areas of “ability to design and conduct research” and “development and production of medicines” were ranked lower. For the latter two categories, industrial pharmacists ranked them higher than did the other five groups.